ASEAN’s environmental consequences: tourism, globalization, and FDI under the pollution haven hypothesis - Md. Ibrahim Kholil; Farian Tahrim; Miguel Angel Esquivias; Md Abdullah Al Mamun; Yessi Rahmawati (Discover Sustainability)
Abstract Environmental degradation mitigation has become a critical ecological and economic concern since the Kyoto Earth Summit in 1997 and the Paris Agreement in 2015. Yet, economic considerations continue to be a top focus. Globalization, urbanization, rapid economic growth, foreign direct investment (FDI), and tourist arrivals have put tremendous strain on natural resources, speeding climate change and exacerbating ecological disasters, especially in some nations, without considering environmental quality. This study examines the intertwined dynamics of FDI, urbanization, tourism, total patents, and globalization on the ecological footprint across nine selected Southeast Asian (ASEAN) countries from 1995 to 2020. Employing canonical cointegration regression (CCR), dynamic ordinary least squares (DOLS), and fully modified ordinary least squares (FMOLS) for baseline assessment, along with quantile regression for robustness, this research provides substantial insights. The results confirm the validity of the pollution haven hypothesis, revealing that FDI reduces environmental quality in ASEAN. Similarly, urbanization, tourism, and total patents have significant positive coefficients, signifying negative environmental impacts. Conversely, GDP and globalization have emerged as key factors in mitigating the ecological footprint. To achieve the sustainable development goals in ASEAN, policies on FDI, urbanization, and tourism must be designed to balance economic growth with environmental quality.